Introduction to Sociocybernetics (Part 1): Third order cybernetics and a basic framework for society - Mancilla, Roberto Gustavo (Journal of Sociocybernetics, 2013)
The purpose of this paper is to initiate the efforts towards an idea of a third order in cybernetics. Second order cybernetics will be used as a biological basis for social processes. Third order studies mutually observing systems, which endows them features of observed and observing systems. Also, while first cybernetics deals with allopoietic machines, and second with autopoietic or living machines, the object of analysis of third cybernetics is language as a cognitive machine that creates a common domain of interaction between living systems in order to interact. These types of machines are abstract mechanisms that have a basis in the human brain and that store, retrieve, process and create information, and as such is both allopoietic and autopoietic; therefore, cognitive machines are omnipoietic. This paper will also account for the creation of social reality by means of a collective assignation of functions by means of speech acts and will use the philosophical scholarship of John Searle to achieve this purpose. Also, society will be analyzed under the lens of complex systems theory. Searle’s idea of social ontology explains Society on a micro level; the meso level is studied by social systems and complex systems theory enables the study of society from a macro perspective.